2020
DOI: 10.1007/s10518-020-00969-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental seismic response of a resilient 3-storey post-tensioned timber framed building with dissipative braces

Abstract: With the increased number of multi-storey buildings in seismic areas, research efforts have been focused on developing earthquake resilient systems, such as low-damage techniques based on the combination of post-tensioning and dissipating devices. This paper describes the experimental study performed on a 3-storey post-tensioned timber framed (Pres-Lam) building equipped with energy dissipating systems. The testing project consisted of three phases adopting different configurations of the experimental model: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Di Cesare et al (2017) developed a similar idea using long, prefabricated laminated timber connected by PT steel tendons or bars. Subsequently, Di Cesare et al (2020) experimentally confirmed the seismic performance of a three-dimensional, three-story timber building designed using a combination of rocking timber beam–column joints and replaceable hysteretic dampers. Rocking timber wall panels that resembled post-tensioned rocking concrete walls were also proposed and experimentally studied (Ganey et al, 2017; Moroder et al, 2018; Newcombe et al, 2008; Sarti et al, 2016; among others).…”
Section: Self-centering Rocking Systemsmentioning
confidence: 80%
“…Di Cesare et al (2017) developed a similar idea using long, prefabricated laminated timber connected by PT steel tendons or bars. Subsequently, Di Cesare et al (2020) experimentally confirmed the seismic performance of a three-dimensional, three-story timber building designed using a combination of rocking timber beam–column joints and replaceable hysteretic dampers. Rocking timber wall panels that resembled post-tensioned rocking concrete walls were also proposed and experimentally studied (Ganey et al, 2017; Moroder et al, 2018; Newcombe et al, 2008; Sarti et al, 2016; among others).…”
Section: Self-centering Rocking Systemsmentioning
confidence: 80%
“…At lower seismic intensities (up to 25% -SLE) no significant variations of drift between the three testing configurations were observed, because the hysteretic devices remained substantially elastic. At higher PGA levels the dissipative bracing systems of BF model a significant reduction of storey drift was observed, with a slightly increase of base shear, due to the stiffness of the bracing system [15]. In particular at 100% of PGA the drift reduced of about 30% than the DF configuration.…”
Section: Global Seismic Responsementioning
confidence: 91%
“…The experimental model was a 3-D, 3-storey, 2/3 scaled post-tensioned glulam timber frame characterized by single bays in both directions, with dimensions in plant of 4 m x 3 m and inter-storey height of 2 m [14][15]. The prototype model was designed according to European code [16] for office use at first and second floors (live load of Q = 3 kPa) and considering a rooftop garden load (Q = 2 kPa).…”
Section: Experimental Modelmentioning
confidence: 99%
See 2 more Smart Citations